Heat Equations Associated with Weinstein Operator and Applications - Hatem Mejjaoli (Journal of Function Spaces and Applications)
We establish a characterization for the homogeneous Weinstein-Besov spaces via the Weinstein heat semigroup. Next, we obtain the generalized Sobolev embedding theorems.